2021
DOI: 10.1155/2021/7174287
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of E-64d in Hippocampal Excitotoxic Neuronal Injury Induced by Glutamate in HT22 Hippocampal Neuronal Cells

Abstract: Epilepsy is the most common childhood neurologic disorder. Status epilepticus (SE), which refers to continuous epileptic seizures, occurs more frequently in children than in adults, and approximately 40–50% of all cases occur in children under 2 years of age. Conventional antiepileptic drugs currently used in clinical practice have a number of adverse side effects. Drug-resistant epilepsy (DRE) can progressively develop in children with persistent SE, necessitating the development of novel therapeutic drugs. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…First, aloesone was selected as the target compound and its anti-seizure effect was determined. The imbalance of glutamatergic and GABAergic neurons is related to epileptogenesis, and glutamate is a vital neurotransmitter mediating seizure-associated cell death via oxidative stress or excitotoxicity (Coyle and Puttfarcken, 1993;Xie et al, 2021). Our results demonstrated that aloesone alleviated glutamate-induced neuronal injury by reducing the intracellular levels of ROS and inhibiting the early apoptosis of neurons.…”
Section: Aloesone Inhibited Ptz-induced Acute and Chronic Seizuresmentioning
confidence: 59%
“…First, aloesone was selected as the target compound and its anti-seizure effect was determined. The imbalance of glutamatergic and GABAergic neurons is related to epileptogenesis, and glutamate is a vital neurotransmitter mediating seizure-associated cell death via oxidative stress or excitotoxicity (Coyle and Puttfarcken, 1993;Xie et al, 2021). Our results demonstrated that aloesone alleviated glutamate-induced neuronal injury by reducing the intracellular levels of ROS and inhibiting the early apoptosis of neurons.…”
Section: Aloesone Inhibited Ptz-induced Acute and Chronic Seizuresmentioning
confidence: 59%
“…Glutamate, a neurotransmitter released by excitatory neurons, is important in various of physiological and pathological brain processes [ 8 , 9 ]. It has been extensively demonstrated that glutamate-mediated excitotoxicity contributes to the neurobiology of epileptic seizures [ 10 ]. Convincing evidence suggests that sustained elevation of extracellular glutamate promotes epileptic seizures and is considered the primary cause of excitotoxicity or neuronal death during seizures [ [11] , [12] , [13] ].…”
Section: Introductionmentioning
confidence: 99%